ADAPTATION POTENTIAL AND ITS IMPROVEMET POSSIBILITIES IN FIRST YEAR STUDENTS AT PHYSICAL TRAINING CLASSES - Kuznetsov, Igor; Burov, Alexander; Kachanov , Igor; Potievskaya, Vera; Popov, Sergey (Revista Inclusiones, 2020)
The rationale for this study is to evaluate adaptation potential in students and to develop a training program for optimization of their functional status and physical work capacity. Scientific and methodical literature review, questionnaire survey, pedagogical experiment, physical fitness testing, methods of mathematical statistics. Four health status and physical fitness uniform groups were formed: 1st, 2nd, 3rd and reference. The parameters from the test groups were compared with the parameters from the reference group, where students had high adaptation potential and physical fitness. The students from the 3rd group had significant increase of speed and power characteristics; pull ups, run broad jumping and grenade throwing results were more informative on speed and power characteristics - the boys showed average results. “Trekrezan” therapy increased the efficiency of locally chosen means of general endurance improvement, which was confirmed by the tests like 1000 m running and 12-minute Cooper’s test. The results of the tests, that evaluated organism functional capacities, showed significant improvement of heart rate and maximal oxygen consumption values. The level of functional Indexes of Ruffier, Skibinsky and Shapovalova increased to “average” and “above average”. Mean value of adaptation potential was equal to 4 points, which was out of the “risk” zone. Individual “additional exercises” contributed to the improvement of functional status, physical fitness and physical work capacity. Activation of the necessary adaptation elements provided compensatory reactions to the training conditions. “Trekrezan” enhanced the efficiency of the developed health improving training program and increased adaptation potential.